POPULARIZATION OF SCIENCE FICTION: FORMULA ANALYSIS ON ELLE McNICOLL’S NOVEL SHOW US WHO YOU ARE - Akbar, Rifqi (Universitas Islam Sumatera Utara (UISU), 2023)
This research is the formula analysis of popularization of science fiction in representing the neurodivergent character, Cora, in Show Us Who You Are. The novel, exposes the female autistic who would be the next hologram creation of Pomegranate’s experimentation. The method used in this study is an inductive-qualitative approach with comprehensive data collection and analysis that generate arguments and critical thinking. The material object used is the novel Show Us Who You Are written by Elle McNicoll, while the formal object is the formula put forward by Raymond Williams about conventions and inventions in the science fiction genre. The combination of science fiction and middle grade makes Elle McNicoll's work unique in reconstructing the romanticization of neurodivergent character from the neurodivergent perspective. Thus, these innovations are presented in various formulas which deconstruct the binary narrative through feminist critique in soft SF formed by the author in the delivery of an inclusive neurodiversity movement.